Couples Therapy Delivered Through Videoconferencing: Effects on Relationship Outcomes, Mental Health and the Therapeutic Alliance - Kysely, Andrea; Bishop, Brian; Kane, Robert Thomas; McDevitt, Maryanne; De Palma, Mia; Rooney, Rosanna (Frontiers in Psychology, 2022)
Changing technology, and the pervasive demand created by a greater need in the population for access to mental health interventions, has led to the development of technologies that are shifting the traditional way in which therapy is provided. This study investigated the efficacy of a behavioural couples therapy program conducted via videoconferencing, as compared to face-to-face. There were 60 participants, in couples, ranging in age from 21 to 69 years old. Couples had been in a relationship for between one to 49 years. The 30 couples were randomly allocated to the face-to-face or videoconferencing group. They all took part in Couple CARE – a couples behavioural education program which promotes self-change in order to increase relationship satisfaction. The six session manualised intervention was offered in an identical manner to all clients, in each condition. Data analysis was based on several questionnaires completed by each couple at pre, post and 3-months follow-up. Results showed that therapeutic alliance ratings did not differ between groups, but increased significantly over time for both groups. Additionally, the results indicated improvements in relationship satisfaction, mental health, and all other outcome scores over time, which did not differ based on condition. This study uniquely contributes to the literature exploring the use of technology to provide therapy. Specifically, the study provides evidence for couples therapy via videoconferencing as a viable alternative to face-to-face interventions, especially for those couples who may not have access to the treatment they require. It is anticipated that the results of this study will contribute to the field of online therapy, and add to fostering confidence in agencies to allow expansion of services conducted via videoconferencing.